Introduction: Science, race and Nazism - Pedro Jesús Teruel (Mètode Science Studies Journal: Annual Review)
«We cannot put our lives right in retrospect; we must go on living with the past. We can put ourselves right, however». This sentence by Reiner Kunze opens a powerful testimony: that of Traudl Junge, Adolf Hitler’s very young secretary from December 1942 until the dictator’s death on 30 April 1945. In her book Bis zur letzten Stunde (published in English as Until the final hour: Hitler’s last secretary), Junge recounts how she gained access to the intimate circle of a man who – she would later realise – had committed monstrous acts beyond any known measure of inhumanity.